Recent Advances in Computational Intelligence - Kumar, Raman; Wiil, Uffe Kock.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book comprehensively addresses computational intelligence, including the theories, methodologies and techniques underlying this evolving field, as well as its potential uses in various domains across the entire spectrum of the sciences (the natural sciences, health sciences, engineering, social sciences, and humanities) and in various types of business. Computational intelligence is rapidly spreading into all kinds of products and services. This calls for the adaptation of existing theories, methodologies and techniques - and the development of wholly new ones - to ensure the successful implementation of new intelligent products and services in various domains related to public organizations, businesses and everyday life. This book gathers contributions from various experts working on different aspects and implementations of computational intelligence, which address new developments in theory, analytical and numerical simulation and modeling, experimentation, deployment and case studies, results of laboratory or field operational tests, and ongoing advances in computational intelligence. It is intended for a broad audience, including researchers, engineers, policymakers, industry experts, and students, offering these readers essential information on and new inspirations regarding the potential of computational intelligence.
Smart Inventory Management using Electronic Sensor Based Computational Intelligence -- Computational Intelligence for Data Analytics -- Review on Current Trends of Deep Learning -- A Variant of Secret Sharing Protected with Poly-1305 -- Enhancing Gadgets for Blinds through Scale Invariant Feature Transform -- A Study to Renovate Image Data using Data Analytics Methodologies -- Video Streaming Communication Over Vanet -- Autonomous Agents - Beginnings, Innings and Where We are Headed.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence